Dzieje obyczajow w dawnej Polsce : wiek XVI-XVIII - Bystron, Jan Stanislaw, 1892-1964.; Tazbir, Janusz (Warszawa : Panstwowy Instytut Wydawniczy, 1994)
A history of customs in old Poland from the 16th to the 18th centuries.
Includes bibliographical references and indexes.
Keywords: Poland -- Social life and customs -- To 1795.; Poland -- Civilization -- To 1795.; Poland -- History -- 16th century; Poland -- History -- 17th century; Poland -- History -- 18th century